The Effect of Walking Speed on Multisegment Spine Coordination and Control in Adolescent Idiopathic Scoliosis: Multiple Single-Subject Analysis Using Colour Map Visualisation...International Research Society of Spinal Deformities (IRSSD 2026), June 18-20, 2026, Novi Sad, Serbia. - NEEDHAM, Robert A.; HEALY, Aoife; LAZIC, Filip; JEVTIC, Nikola; CHOCKALINGAM, Nachiappan (Studies in Health Technology & Informatics, 2026)
Adolescent idiopathic scoliosis (AIS) is a spinal deformity that can affect dynamic movement and postural stability. Gait analysis research in AIS typically involves pooling group data, which may obscure clinically meaningful inter-individual differences in kinematic responses. This study examined the effect of walking speed on multi-segment spine coordination in adolescents with AIS using a multiple single-subject analysis approach incorporating coordination profiling and vector coding visualisation techniques. Ten females with a confirmed diagnosis of AIS (mean age 14 years, SD = 1.50) walked barefoot at a preferred walking speed (PWS: 1.09 ± 0.13 m/s) and a fast-walking speed (FWS: 1.44 ± 0.15 m/s). Marker trajectory data were collected using a ten-camera motion capture system and analysed using coupling angle mapping, segmental dominance profiling, and inter-data point range of motion (IDROM). Coupling angle mapping revealed predominantly in-phase coordination patterns at both walking speeds, which were broadly consistent across the gait cycle for all participants. However, considerable inter-individual variability in the distribution and timing of coordination patterns was observed, with no uniform response to the change in walking speed evident across the cohort. Segmental dominance values were broadly stable across speeds for most participants, yet inter-individual differences were apparent, with some participants demonstrating greater proximal segmental dominance and others a more balanced inter-segmental contribution. A general trend of increased inter-segmental motion at FWS; however, this response was not universal across all participants. These findings highlight the heterogeneous nature of spinal coordination in AIS and demonstrate the value of multiple-single-subject analysis colour maps in identifying clinically meaningful individual responses that would otherwise be concealed by group-level averaging.